Phytoplankton Response to Different Light Colors and Fluctuation Frequencies - Neun, Sebastian; Hintz, Nils Hendrik; Schröder, Matthias; Striebel, Maren (Frontiers in Marine Science, 2022)
The natural environment of phytoplankton is variable in manifold ways. Light, as essential resource for photosynthetic phytoplankton, fluctuates in its intensity (quantity) as well as spectrum (quality) over great temporal scales in aquatic ecosystems. To elucidate the significance of temporal heterogeneity in available light spectrum for phytoplankton, we analyzed the growth of four marine North Sea species (chlorophyte Tetraselmis sp., cryptophyte Rhodomonas salina, cyanobacteria Pseudanabaena sp., raphidophyte Fibrocapsa japonica), in monoculture as well as the dynamics of these species in pairwise competition experiments under blue and green light. These species were chosen as they differ in their absorption of light, the colors were chosen to contrast the absorption by chlorophylls (blue), carotenoids (partially green) and phycobiliproteins (green). Light colors were either supplied constantly or along a gradient of fluctuation frequencies (hourly to weekly alternation) between blue and green but always with the same photon flux density. When constantly supplied (no change in color), the color of light led to significant differences in growth rates and carrying capacities of the species, with Pseudanabaena sp. being the only one profiting from green light. Under alternating light color, the maximum growth rate of R. salina was higher with faster light color fluctuations, but lower for Pseudanabaena sp. and did not show significant trends for F. japonica and Tetraselmis sp. Accordingly, competition was significantly affected by the light color treatments, under constant as well as fluctuating supply conditions. However, we did not detect considerable changes in competitive outcomes between fluctuating light colors vs. constant light color supply. As the underwater light in natural ecosystems is rather variable than constant, our results of fluctuations within the light spectrum highlight their frequency-dependent effects on growth and competition. While fluctuating light colors affect the growth and capacity of species, our tested fluctuations did not have major effects on species competition.